Analysis of the efficacy and related factors of ventriculoperitoneal shunt for AIDS with cryptococcal meningitis - Chai, Zhaohui; Shou, Yikai; Mungur, Rajneesh; Gong, Jiangbiao; Zheng, Peidong; Zheng, Jiesheng (Frontiers in Surgery, 2022)
Background Cryptococcus neoformans is an opportunistic pathogen, which is more common in patients with AIDS. Increased intracranial pressure (ICP) is an important complication of cryptococcal meningitis (CM) and affects the therapeutic effect of CM. Objective To evaluate the effect and treatment for the management of ventriculoperitoneal shunt (VPS) in the treatment of AIDS complicated with CM and to analyze the factors associated with VPS and the indices affecting the outcome of CM patients. Methods A retrospective case study was conducted on patients with CM treated in the First Affiliated Hospital of Zhejiang University School of Medicine from 2011 to 2019. The Chi-square test was used for categorical variables and the Student’s t-test was used for continuous variables. Multivariable analysis of baseline factors related to VPS placement was performed with stepwise logistic regression analysis, factors associated with the outcome of these patients were studied by Cox regression analysis, and Kaplan–Meier survival curves were constructed to assess the outcome of patients. Results There were 96 patients with AIDS complicated with CM. VPS had a great effect on the patients, especially those with ICP > 350 mmH2O. The outcome, including the mortality rate and modified Rankin scale (MRS) score of these patients, significantly improved after the placement of VPS. The karnofsky performance status (KPS) scores of patients whose ICP > 350 mmH2O improved from 39.3 ± 21.3 at baseline to 88.7 ± 26.9 at 3 months after VPS, better than those without VPS. Multivariable analysis showed that visual impairment (OR, 0.026; 95% CI, 0.001, 0.567; P =<sans-serif> 0</sans-serif>.021) and ICP > 350 mmH2O (OR, 0.026; 95% CI, 0.002, 0.293; P =<sans-serif> 0</sans-serif>.003) were related elements with the placement of shunt, and KPS score (HR, 0.968; 95% CI, 0.943, 0.993; P =<sans-serif> 0</sans-serif>.013) and ICP > 350 mmH2O (HR, 2.801; 95% CI, 1.035, 7.580; P =<sans-serif> 0</sans-serif>.043) were indices of the outcome of AIDS patients with CM. For patients with ICP > 350 mmHg, Kaplan–Meier analysis showed that the 3-year outcome of patients with VPS was better than that of patients without VPS (P =<sans-serif> 0</sans-serif>.0067). Conclusion VPS was associated with better 3-year survival rates, and postshunt placement complications like infections were rare. The identification of factors related to VPS in the initial diagnosis of CM can contribute to more active management and improve the outcome.